A New 3D Coordination Polymer of Bismuth with Nicotinic Acid N-Oxide. (11th September 2013) - Marandi, Farzin; Pantenburg, Ingo; Meyer, Gerd
Abstract : The new three-dimensional coordination polymer {[Bi(NNO)2 (NO3 )]·1.5H2 O} n (1, NNO − = nicotinate N -oxide) was synthesized and characterized by elemental analysis, IR and 1 H-NMR spectroscopy, as well as single-crystal X-ray diffraction analysis. 1 crystallizes in the monoclinic space group C2/c. The crystal structure consists of a rectangular-shaped grid constructed with NNO linkers. Cavities of a diameter of 7.9–8.3 Å 2 are filled with disordered water molecules. The thermal stability of the compound was evaluated by thermogravimetric analysis.